2016
DOI: 10.2322/tastj.14.pe_121
|View full text |Cite
|
Sign up to set email alerts
|

Bow-Shock Instability and its Control in front of Hemispherical Concave Shell at Hypersonic Mach Number 7

Abstract: In this study, effectiveness of vortex manipulation by using passive control methods at hypersonic flows have been studied to control the bow-shock instabilities in front of negative curvature (concave) hemispherical shell. The force measurement and unsteady center pressure measurements were performed for hemispherical shell with no control and with three kind of passive controls such as spike at the center of cavity, breathing holes at the curved surface and crosswire along the diameter of hemisphere. The flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…For this flowfield, it is assumed that Δz is small when compared to the abscissa range of this tanh function. For a blunt-body model with a convex surface at Mach 7, Vashishtha et al [14] observed Δz to be typically small; large Δz were observed in ~1% of the data. Large Δz were correlated with and attributed to particle strikes.…”
Section: Unsteadiness Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…For this flowfield, it is assumed that Δz is small when compared to the abscissa range of this tanh function. For a blunt-body model with a convex surface at Mach 7, Vashishtha et al [14] observed Δz to be typically small; large Δz were observed in ~1% of the data. Large Δz were correlated with and attributed to particle strikes.…”
Section: Unsteadiness Mechanismmentioning
confidence: 99%
“…There is a small but growing number of experimental studies of hypersonic bow-shock oscillations induced by freestream disturbances [10,11,14,15]. There have been several mathematical analysis and computational studies on freestream-unsteadiness-induced bowshock oscillations [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A hemispherical cavity in front of hypersonic flow is also considered an effective flow control to increase aerodynamic drag and reduce heating at hypersonic flows, but it is also subjected to very highly unsteady flow-field, resulting in uncontrolled lift and side forces [5,6]. Few passive control methods have been suggested for frontal cavity and found effective in controlling the unsteadiness [7]. In active flow control methods, the counter-jet flow [1] has also been found effective method, creating flow spike to push the shock wave away from the blunt nose, but require additional system to inject high-pressure gas into the stagnation zone.…”
Section: Introductionmentioning
confidence: 99%